Science &Amp; Technology Education Library 2004
DOI: 10.1007/978-1-4020-5814-1
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Inquiry and Nature of Science

Abstract: All Rights ReservedNo part of this work may be reproduced, stored in a retrieval system, or transmitted in any form or by any means, electronic, mechanical, photocopying, microfilming, recording or otherwise, without written permission from the Publisher, with the exception of any material supplied specifically for the purpose of being entered and executed on a computer system, for exclusive use by the purchaser of the work. ISBN 978-1-4020-2671-3 (HB) ISBN 978-1-4020-2672-0 (eBook) © 2006 Springer www.springe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 144 publications
(181 reference statements)
0
3
0
1
Order By: Relevance
“…Según lo advierten Justi (2006) y Morales (2010) para aprender sobre la ciencia es necesario comprender su naturaleza, así como identificar que los procesos de modelización son algo fundamental. -Por otra parte, en la actualidad, incluir aspectos acerca de la NdC en futuros profesores de ciencias es considerado una prioridad (Flick y Lederman, 2010). Sin embargo, la discusión se centra en cómo esta debe enseñarse de modo que se generen aprendizajes más profundos, no solo de la propia NdC, sino de los contenidos de base de las disciplinas científicas objeto de enseñanza.…”
Section: Aproximación a La Naturaleza De La Ciencia (Ndc)unclassified
“…Según lo advierten Justi (2006) y Morales (2010) para aprender sobre la ciencia es necesario comprender su naturaleza, así como identificar que los procesos de modelización son algo fundamental. -Por otra parte, en la actualidad, incluir aspectos acerca de la NdC en futuros profesores de ciencias es considerado una prioridad (Flick y Lederman, 2010). Sin embargo, la discusión se centra en cómo esta debe enseñarse de modo que se generen aprendizajes más profundos, no solo de la propia NdC, sino de los contenidos de base de las disciplinas científicas objeto de enseñanza.…”
Section: Aproximación a La Naturaleza De La Ciencia (Ndc)unclassified
“…This research has shown that teaching scientific disciplines (i.e., physics, mathematics, chemistry and technical matters)-through Nature of Science also by means of an historical apparatus -has a positive impact on the students understanding (Cfr. McComas et al 1998;Flick and Lederman 2006). Moreover, recent studies have tested the impact of studying historical texts (Macale 2018) and replicating experiments; in particular Joule's paddle wheel experiment (Cfr.…”
Section: Final Remarks On Nosmentioning
confidence: 99%
“…However, using sensing technologies and other wireless tools is currently preferred in science activities. In particular, the use of sensor probes occupies a significant place in science education as, instead of only stimulating science and scientific data, they provide the direct opportunity of making real time measurements (Novak & Krajick, 2006).…”
Section: Mobile Learningmentioning
confidence: 99%
“…On the other hand, various difficulties were being reported in terms of motivation, accessibility of investigation techniques, background knowledge, management of extended activities, and the practical constraints of the learning context (Edelson, Gordon & Pea, 1999). Later, with the development of motivating investigative techniques used in the inquiry process such as probes, modeling, Web 2.0, hypermedia artifacts, hand-held computers, applications, and visualization tools, technology began to be transferred into laboratory practices much more effectively (Novak & Krajick, 2006). As well as these developments which facilitate laboratory practices, mobile learning brings new understanding of the inquiry based laboratory practices.…”
Section: Technology and Inquiry Based Laboratory Practicesmentioning
confidence: 99%